Influence of the Nature of Aminoalcohol on ZnO Films Formed by Sol-Gel Methods - Anna Vilà; Alberto Gómez-Núñez; Xavier Alcobé; Sergi Palacios; Teo Puig Walz; Concepción López (Nanomaterials, 2023)
Here we present comparative studies of: (i) the formation of ZnO thin films via the sol-gel method using zinc acetate dihydrate (ZAD), 2-methoxyethanol (ME) as solvent, and the aminoalcohols (AA): ethanolamine, (S)-(+)-2-amino-1-propanol, (S)-(+)-2-amino-3-methyl-1-butanol, 2-aminophenol, and aminobenzyl alcohol, and (ii) elemental analyses, infrared spectroscopy, X-ray diffraction, scanning electron microscopy, absorption and emission spectra of films obtained after deposition by drop coating on glass surface, and thermal treatments at 300, 400, 500 and 600 °C. The results obtained provide conclusive evidences of the influence of the AA used (aliphatic vs. aromatic) on the ink stability (prior to deposition), and on the composition, structures, morphologies, and properties of films after calcination, in particular, those due to the different substituents, H, Me, or iPr, and to the presence or the absence of a –CH2 unit. Aliphatic films, more stable and purer than aromatic ones, contained the ZnO wurtzite form for all annealing temperatures, while the cubic sphalerite (zinc-blende) form was also detected after using aromatic AAs. Films having frayed fibers or quartered layers or uniform yarns evolved to “neuron-like” patterns. UV and photoluminescence studies revealed that these AAs also affect the optical band gap, the structural defects, and photo-optical properties of the films.